Recent Advancements in Two-Dimensional Layered Molybdenum and Tungsten Carbide-Based Materials for Efficient Hydrogen Evolution Reactions - K. Karuppasamy; A. Nichelson; Dhanasekaran Vikraman; Jun-Hyeok Choi; Sajjad Hussain; C. Ambika; Ranjith Bose; Akram Alfantazi; Hyun-Seok Kim (Nanomaterials, 2022)
Green and renewable energy is the key to overcoming energy-related challenges such as fossil-fuel depletion and the worsening of environmental habituation. Among the different clean energy sources, hydrogen is considered the most impactful energy carrier and is touted as an alternate fuel for clean energy needs. Even though noble metal catalysts such as Pt, Pd, and Au exhibit excellent hydrogen evolution reaction (HER) activity in acid media, their earth abundance and capital costs are highly debatable. Hence, developing cost-effective, earth-abundant, and conductive electrocatalysts is crucial. In particular, various two-dimensional (2D) transition metal carbides and their compounds are gradually emerging as potential alternatives to noble metal-based catalysts. Owing to their improved hydrophilicity, good conductivity, and large surface areas, these 2D materials show superior stability and excellent catalytic performances during the HER process. This review article is a compilation of the different synthetic protocols, their impact, effects of doping on molybdenum and tungsten carbides and their derivatives, and their application in the HER process. The paper is more focused on the detailed strategies for improving the HER activity, highlights the limits of molybdenum and tungsten carbide-based electrocatalysts in electro-catalytic process, and elaborates on the future advancements expected in this field.